A Comparative Case Study On Outreach And Impact Of The Ikhtiar Loan Scheme And The Development Programme For The Hard-Core Poor In Seberang Perai, Penang - Mahmud, Salma (2006)
Program Pembangunan Rakyat Termiskin (PPRT) dan skim pinjaman ikhtiar, Amanah Ikhtiar Malaysia (AIM)